Generalization of Fuzzy Boundary in Fuzzy Bitopological Spaces - T. Thangam; K. Bageerathi (International Journal of Mathematics And its Applications, 2018)
Focus of this paper is to introduce the concept of fuzzy $(τ_{i}, τ_{j})$-boundary and fuzzy $\mathfrak{C}$-$(τ_{i}, τ_{j})$-boundary in fuzzy bitopological space where $\mathfrak{C}: [0,1] → [0,1]$ is a complement function. Several examples are given to illustrate the concepts introduced in this paper.